2009
DOI: 10.1164/rccm.200804-608oc
|View full text |Cite|
|
Sign up to set email alerts
|

Obstructive Sleep Apnea, Insulin Resistance, and Steatohepatitis in Severe Obesity

Abstract: Rationale: Obstructive sleep apnea is associated with insulin resistance and liver injury. It is unknown whether apnea contributes to insulin resistance and steatohepatitis in severe obesity. Objectives: To examine whether sleep apnea and nocturnal hypoxemia predict the severity of insulin resistance, systemic inflammation, and steatohepatitis in severely obese individuals presenting for bariatric surgery. Methods: We performed sleep studies and measured fasting blood glucose, serum insulin, C-reactive protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
146
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(161 citation statements)
references
References 58 publications
9
146
0
6
Order By: Relevance
“…[29] Although there is no single standard cutoff point for abnormal liver function tests levels, the most commonly used criterion is a value of ≥40 U/L for both ALT and AST. [30] Few authors like Polotsky et al [31] and Aron-Wisnewsky et al [32] similar to the present study reported normal range serum ALT and AST values in bariatric population with a BMI >45, regardless of the severity of OSA and NASH. It is worthy to note that liver biopsy of patients in both studies showed evidence of NASH with ballooning and liver fibrosis.…”
Section: Discussionsupporting
confidence: 83%
“…[29] Although there is no single standard cutoff point for abnormal liver function tests levels, the most commonly used criterion is a value of ≥40 U/L for both ALT and AST. [30] Few authors like Polotsky et al [31] and Aron-Wisnewsky et al [32] similar to the present study reported normal range serum ALT and AST values in bariatric population with a BMI >45, regardless of the severity of OSA and NASH. It is worthy to note that liver biopsy of patients in both studies showed evidence of NASH with ballooning and liver fibrosis.…”
Section: Discussionsupporting
confidence: 83%
“…Chronic intermittent hypoxia exposure would be the most important pathogenetic mechanism leading to NASH, as shown by studies in animal models [53]. To date, at least two studies have assessed liver morphology in humans in relation to OSA severity [33,54]; both analysed liver biopsies obtained in morbidly obese patients undergoing bariatric surgery and reported a strong association between severity of nocturnal intermittent hypoxia and liver abnormalities (steatosis and fibrosis).…”
Section: Osa and Liver Damagementioning
confidence: 99%
“…3,4 Many studies have demonstrated that OSAS should be diagnosed and treated at an early stage, 5,6 because OSAS can cause serious traffic accidents, 7 long-term hypoxic stress, 8 a pro-inflammatory state, 9 and endothelial dysfunction 10 in various organs. Although some patients with undiagnosed OSAS may visit an otolaryngology department to be treated for their snoring, other patients may visit a psychiatry department for a sense of malaise or a urology department for nocturia or erectile dysfunction.…”
Section: Introductionmentioning
confidence: 99%